Tinjauan Tanda Visual Yogyakarta Dalam FTV ‘Ada Cinta Diantara Kita’ - Danu Widiantoro; Siti Lenggogeni (AKSA: Jurnal Desain Komunikasi Visual, 2017)
Film is one part of creative economic development in Indonesia. FTV is one form of film development that lifts the story of everyday life into a glass screen. FTV entitled " Ada Cinta Diantara Kita" is a film produced in 2017, aired by national television station SCTV with. took the filming location around the city of Yogyakarta. One of the most important things in making FTV "Ada Cinta Diantara Kita" is a visual sign of the visual identity of Yogyakarta that appears as the background scene in FTV. The presence of these signs is interesting to examine the extent to which it is able to support the visualization of the Javanese cultural atmosphere of Yogyakarta in each display of FTV images and signs such as what is used to support the achievement of making the above FTV.